Modernization of Two-Phase Oil and Gas Separator - Rafikovna Ganieva, Guzel; Niradgnani, Putu Aunda (Nexo Revista Científica, 2020)
Separators play an important role in the basis of the technological scheme and field preparation of oil and gas. Separation is the process of oil separation from gas. Depending on the requirements for the feedstock, separators are distinguished according to the principle of operation and purpose. In this paper, the company "PT Pertamina EP Asset 3 Subang", Indonesia (Nirajani) is considered as an example. Dimensions, efficiency, reliability of equipment, capital and operating costs are the main indicators of separator work and productivity. "Subang PT Pertamina EP Asset 3 Subang" collection station has 3 horizontal two-phase separators (high pressure, low pressure and test separator). In 2020, it is planned to increase the extraction of raw materials. In this regard, the aim of this work is to modernize the existing two-phase horizontal separator operated at the field. To achieve this goal, it is necessary to study the design of the existing separator, and calculate its performance (Nirajani). After all the calculations, it is necessary to choose a separator suitable for performance. Modernization of the existing separator is economically feasible for this enterprise.